Domestic Debt and Economic Growth in Nigeria: An ARDL Bounds Test Approach - Ibrahim Ayuba K.; Khan Shazida Mohd (Economics and Business, 2019)
The study examines the long-run relationship between domestic debt and the fiscal policy of economic growth in Nigeria in the period from 1981 to 2013 owing to government reforms in the financial system, particularly due to the establishment of the Debt Management Office (DMO) in 2000 and a new fully funded pension fund scheme, both of which resulted in a resurgence of the debt market. The issue that is often raised is the doubt regarding the stability of the debt and its likely implications for the economy, as well as the unpleasant consequences for the government embarking on consolidation. The study employs the autoregressive distributed lag (ARDL) approach and the bounds test as proposed by Narayan (2005), anchored on the perspective of the endogenous growth theory. The results reveal that although overall the adverse negative domestic debt hurts the economy, it has a positive effect on the total aggregate government revenue and economic growth in Nigeria in the research period. Furthermore, the paper develops a system to assess the speed of the adjustment mechanism coefficient in an error correction model (ECM).